2008
DOI: 10.1080/01635580801993751
|View full text |Cite
|
Sign up to set email alerts
|

Food Frequency Questionnaires and Overnight Urines Are Valid Indicators of Daidzein and Genistein Intake in U.S. Women Relative to Multiple 24-h Urine Samples

Abstract: Data regarding convenient, valid methods for measuring U.S. isoflavone intake are limited. We evaluated a soy food questionnaire (SFQ), the Willett food frequency questionnaire (FFQ), and overnight urine samples relative to excretion in 24-h urine samples. We also described intake among women in a high-risk program for breast or ovarian cancer. Between April 2002 and June 2003, 451 women aged 30 to 50 yr with a family history of breast or ovarian cancer completed the SFQ and FFQ. Of them, 27 provided four 24-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Plasma and urine concentrations were also consistent with those previously reported in individuals consuming a Western diet (7, 8). However, we failed to show a correlation between the soy isoflavones from the Soy FFQ and plasma and urine concentrations for genistein and daidzein.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Plasma and urine concentrations were also consistent with those previously reported in individuals consuming a Western diet (7, 8). However, we failed to show a correlation between the soy isoflavones from the Soy FFQ and plasma and urine concentrations for genistein and daidzein.…”
Section: Discussionsupporting
confidence: 89%
“…The majority of subjects enrolled in this study were male, (87%) and older, with a median age of 71 (range 46-97), consistent with individuals at risk for bladder cancer. Another potential explanation for the difference is that the Soy FFQ was validated for plasma concentrations and we also evaluated urine, although other Soy FFQs have been validated for urine concentrations (7, 8). …”
Section: Discussionmentioning
confidence: 99%
“…In another US population study, positive correlations were demonstrated between self-reported soy intake and excretion of urinary isoflavones ( r = 0.52, p < 0.001 for dietary recall and r = 0.29, p < 0.01 for FFQ) [ 42 ]. In a US study ( n = 451 women) [ 43 ], 24-h urine sample measures were shown to be strongly correlated with overnight urine excretion for daidzein ( r = 0.84) and genistein ( r = 0.93). The 24-h urine sample measures were also correlated with soy food questionnaire (SFQ) estimates of daidzein ( r = 0.48) and genistein ( r = 0.54) intake [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biomarkers of intakes were not used in the studies reviewed. Although there have been several recent studies of flavonoid biomarkers 134–139 and several studies validating isoflavone intakes, 140–153 very few studies 154–156 validating other flavonoids have been done that examined blood or urine samples for biomarkers 157,158 . Thus, the errors in flavonoid intake assessment may have been considerable.…”
Section: Discussionmentioning
confidence: 99%